2014
DOI: 10.4317/medoral.18936
|View full text |Cite
|
Sign up to set email alerts
|

Burkitt lymphoma of the jaws in the Amazon region of Brazil

Abstract: Objectives: To describe the clinicopathologic and immunohistochemical features of Burkitt’s lymphoma of the jaws in 7 patients of Northern Brazil. Study Design: Clinical data concerning gender, age, affected site, clinical presentation, symptomatology and follow-up were collected from the clinical files. Histopathology was complemented with a broad immunohistochemical panel and in situ hybridization for Epstein-Barr virus (EBV). Results: Most of the patients were infants and 5 out of 7 were males. The mandibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 24 publications
6
21
1
Order By: Relevance
“…Socioeconomic improvement in Brazil turned into a decreased incidence from 87% to 46% in a 54 year period [ 32 ]. A similar picture emerges for EBV-positive BL, since this disease shows features of endemic BL in particularly underdeveloped regions, for instance, 76–100% in North Brazil [ 36 , 56 ], while it resembles more the sporadic form in the South of Brazil, Chile and Argentina [ 114 ]. Fewer driver mutations, especially among genes with roles in apoptosis, were demonstrated in EBV-positive BL from USA and Uganda, suggesting a specific BL phenotype, irrespective of geographic origin [ 494 ].…”
Section: Discussionmentioning
confidence: 75%
“…Socioeconomic improvement in Brazil turned into a decreased incidence from 87% to 46% in a 54 year period [ 32 ]. A similar picture emerges for EBV-positive BL, since this disease shows features of endemic BL in particularly underdeveloped regions, for instance, 76–100% in North Brazil [ 36 , 56 ], while it resembles more the sporadic form in the South of Brazil, Chile and Argentina [ 114 ]. Fewer driver mutations, especially among genes with roles in apoptosis, were demonstrated in EBV-positive BL from USA and Uganda, suggesting a specific BL phenotype, irrespective of geographic origin [ 494 ].…”
Section: Discussionmentioning
confidence: 75%
“…6,8 Numerous studies in the literature have reported BL involving sites throughout the whole body; however, only a few reports focusing exclusively on BLHN have been described. 9,10 Thus, we conducted a retrospective analysis to investigate the clinicopathological features, immunophenotype, and EBV infection status of BLHN in patients from South Africa, Guatemala, and Brazil, in order to compare possible differences between regions. This study forms part of a special issue published by the Journal of Oral Pathology and Medicine covering the most important aspects of haematolymphoid lesions and neoplasms affecting the oral cavity and neighboring structures.…”
Section: Introductionmentioning
confidence: 99%
“…9,19,20 Additionally, existing studies of BL have been limited by small sample sizes or only included subsets of ages, either adults or children. 10,21 …”
mentioning
confidence: 99%
“…3,7,8 All three forms of BL are responsive to treatment in children provided they have access to effective treatment. 9,10 The use of brief intensive chemotherapy in adults is generally effective, however, BL is commonly misclassified as other forms of NHL especially diffuse large B cell lymphoma and hence may not be treated appropriately resulting in very poor prognosis. [11][12][13][14] Studies of BL have largely focused on African/endemic disease because it is more common, easier to diagnose, and has a disfiguring nature and unique characteristics as aforementioned.…”
mentioning
confidence: 99%
See 1 more Smart Citation